Culture Spatial On Eid AI-FITR Celebration in Pegayaman Village Bulelelng Bali - Ni G.A. Diah Ambarwati Kardinal (IAHN-TP Palangka Raya, 2022)
The formation of a residential environment is basically determined by various factors. Among them is the culture of the local community. Culture is unique, from one place to another can have very different meanings. This uniqueness can be found in Pegayaman Village, one of the oldest Muslim village in Bali, which has existed since the days of the Buleleng kingdom during the reign of Ki Barak Panji Sakti (Early 16th Century). After living for a long time, acculturation took place between Balinese Hindu traditions and Islamic traditions in Pegayaman. This acculturation can be seen in the Eid celebrations in Pegayaman Village, which we do not find in other villages. The cultural spatial created during the Eid celebration is the hallmark of the Pegayaman village cultural spatial. Identification of the cultural spatial formed during the Eid celebration is carried out by superimposing the cultural spatial on the macro and mezzo scales that are formed during the series of celebrations so that a complete cultural space is obtained at the Eid Celebration. Cultural spatial in the series of Eid al-Fitr celebrations are mosques, schools, madrasahs, mushola, orphanages, cemeteries, road spaces, and Penghulu houses. During the month of Ramadan, the mosque becomes a very important cultural spatial because it is used for 24 hours. There is a lost tradition that is usually carried out during Ramadan due to the increasing population and technological advances.